Culturological approach to the Linguistic personality formation of Agrarian affairs specialist- to-be (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to the main methodological basis of culturological approach to the linguistic personality formation of agrarian affairs specialists-to be and the methods of its realization in the context of «Ukrainian language according to the vocational guidance» training course.
Keywords: culturological approach; linguistic personality; linguistic worldview; concept; culturological tasks